2015
DOI: 10.3390/systems3040211
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Learning to Control Dynamic Uncertainty

Abstract: Abstract:In dynamic environments, when faced with a choice of which learning strategy to adopt, do people choose to mostly explore (maximizing their long term gains) or exploit (maximizing their short term gains)? More to the point, how does this choice of learning strategy influence one's later ability to control the environment? In the present study, we explore whether people's self-reported learning strategies and levels of arousal (i.e., surprise, stress) correspond to performance measures of controlling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…The number of participants allocated to the frequent condition was less than that of the intermittent feedback conditions, for the following reasons. Considerable prior work (Osman et al, 2015;Osman & Speekenbrink, 2011 using the same task design has shown that the pattern of responses to frequent feedback in exact same stable dynamic decision-making tasks used presently is consistent, particular when participants are exposed to the same length of training trials (i.e. 100 training trials), as is the case with the present set of experiments.…”
Section: Predictions Generated From the Modelsupporting
confidence: 56%
See 3 more Smart Citations
“…The number of participants allocated to the frequent condition was less than that of the intermittent feedback conditions, for the following reasons. Considerable prior work (Osman et al, 2015;Osman & Speekenbrink, 2011 using the same task design has shown that the pattern of responses to frequent feedback in exact same stable dynamic decision-making tasks used presently is consistent, particular when participants are exposed to the same length of training trials (i.e. 100 training trials), as is the case with the present set of experiments.…”
Section: Predictions Generated From the Modelsupporting
confidence: 56%
“…From this we introduce the Single Limited Input, Dynamic Exploratory Response Model (SLIDER, Osman, Glass, & Hola, 2015). At the heart of most computational models of dynamic decision-making is a reinforcement learning component.…”
Section: Computational Modeling Of Dynamic Decision-makingmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore have to build upon uncertain and incomplete information. The impact of uncertainty in decision making is well described in [4,5]. Madni and Jackson [6] describe this problem in the field of resilience engineering.…”
Section: Introductionmentioning
confidence: 99%